Pharmacokinetics of lactosaminated recombinant human growth hormone in mice - Li Yun-Chun; Guan Chang-Tian; Zhao Ke-Qing; Chen Ze-Lian; Li Tong-Ling (Acta Pharmacologica Sinica, 2016)
Aim: To study the pharmacokinetic characteristics of lactosaminated recombinant human growth hormone (hGH-L) in mice. Methods: The biodistribution was studied with in vivo radioactive tracer technique. The pharmacokinetics was investigated by radioimmunoassay (RIA) method of hGH-L. The results were compared with that of recombinant human growth hormone (hGH). Results: 125I-hGH-L has remarkable livertaxis. The area under drug concentration-time curve (32686.9 microg . min . L-1) in blood and serum mean residence time (21.4 min) of hGH-L are less than that of hGH (36913.1 microg . min . L-1 and 24.9 min) (P < 0.05). In target organ liver, hGH-L distribution half life (1.8 min) and elimination half life (11.1 min) are shorter than that of hGH (2.1 min and 27.7 min) (P < 0.05). The area under drug concentration-time curve (17621.9 microg . min . L-1) of hGH-L is bigger than that of hGH(12148.2 microg . min . L-1) (P < 0.05) in liver. Conclusion: The pharmacokinetic parameters of hGH-L has obvious advantage over that of hGH.